(untitled) (Международный научный журнал «Инженер», 2026)
Currently, the basic matrix structures for chemical modification and production of ion exchangers are styrene and acrylic copolymers cross-linked with divinylbenzene. By adjusting the copolymerization conditions, it is possible to obtain not only a given size, but also other parameters of the initial polymer granules important for the synthesis of ion exchangers, primarily porosity. Copolymers of styrene with divinylbenzene are a universal matrix for obtaining both main classes of ion exchangers - cation exchangers and anion exchangers. In this regard, the search for new ion exchangers with a set of valuable indicators is of great practical interest. Therefore, recent research in the field of creating competitive products is aimed at effective methods for modifying existing ion exchangers in order to impart to them improved indicators of such basic properties as increased thermal and chemical resistance, fairly good indicators of kinetic, sorption, and selective characteristics. This, in turn, is solved by using a modern approach to obtaining products and issues of rational use of available initial resources and secondary products of production.